“His Blood be upon Us”: A Textual Exegesis for Popes and Filmmakers - Hanson, K. L. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2008)
In light of the mid-2007 edict of Pope Benedict reinstating an old mass that contains references to “Jewish blindness,” it is appropriate to revisit key passages in the New Testament Gospels, especially the passion narrative, with an eye toward examining the text not only for anti-Jewish/ anti-Semitic content, but for sound exegesis that might to some extent “attenuate” its otherwise vexing implications. An understandable tide of opprobrium has called into question Pope Benedict’s judgment in leading the church at least “one small step” backward, but whether enough scholarly attention has been brought to bear on persistent and underlying issues vis-à-vis anti-Semitism/ anti-Judaism in the Gospels themselves is another matter. Ever since the release of The passion of the Christ, directed by another Catholic of traditional bent, there has been renewed interest in understanding the nature of the most grievous of anti-Semitic charges, namely, “deicide” – the “murder of God.” This research will attempt to provide some serious answers to such problems imbedded in the synoptic tradition and even “mitigate” to some extent the anti-Jewish attitudes fostered in the Gospels, particularly by the account of Jesus’ trial and execution. Of particular focus will be what is perhaps the most troublesome verse in the Matthean account, “Then answered all the people, and said, his blood be on us, and on our children” (Matthew 27:25). An attempt will be made to understand the “evolution of blame” in the “triple tradition” and to reach some helpful conclusions that may effectuate inter-faith dialogue and hopefully, healing.